1981
DOI: 10.1063/1.441506
|View full text |Cite
|
Sign up to set email alerts
|

The structure of an aqueous ammonium chloride solution

Abstract: X-ray measurements have been performed on a 2 molal NH4 Cl solution at 25 °C. The scattering data have been evaluated with the first neighbor model (FNM). These results are compared with molecular dynamics (MD) simulations where the ST2 model for water is employed. The NH4+ is described by a rigid tetrahedron with point charges at the positions of the hydrogen atoms and the Cl− by a Lennard-Jones sphere with an elementary charge at the center. Good agrement has been found between the measurements and the simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Compared to the experimentally observed coordination number of 8, 10 good agreement can then be achieved. In fact, comparison between experiments and theories is not always straightforward because most of the experimental methods for structural analysis have to be performed with solutions of relatively high concentrations, while the theoretical approaches mostly refer to very dilute solutions.…”
Section: Structural Propertiessupporting
confidence: 51%
See 3 more Smart Citations
“…Compared to the experimentally observed coordination number of 8, 10 good agreement can then be achieved. In fact, comparison between experiments and theories is not always straightforward because most of the experimental methods for structural analysis have to be performed with solutions of relatively high concentrations, while the theoretical approaches mostly refer to very dilute solutions.…”
Section: Structural Propertiessupporting
confidence: 51%
“…8 -20 Of particular interest, recent NMR measurements 6,8 have shown that NH 4 ϩ rotates quite fast in aqueous solution, despite the expected strong hydrogen bonding between the NH 4 ϩ and its surrounding water molecules. To explain such surprising phenomenon, several rotational mechanisms have been proposed based on either ab initio geometry optimizations [11][12][13] as well as Monte Carlo (MC) 14 and molecular dynamics (MD) 10,[15][16][17][18][19][20] simulations. Most of the previous studies have provided useful information on the dynamical properties of the hydrated NH 4 ϩ , such as its fast diffusive rotational motion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of x-ray measurements and MD simulations has been shown to be a good way to elucidate structures of aqueous electrolyte solutions [6,7]. Therefore, in a subsequent paper [8] new x-ray measurements on a Lil solution are reported and compared with the structural properties discussed here.…”
Section: Introductionmentioning
confidence: 99%